2023
DOI: 10.3389/fimmu.2023.1107844
|View full text |Cite
|
Sign up to set email alerts
|

IL-32 is induced by activation of toll-like receptors in multiple myeloma cells

Abstract: Multiple myeloma (MM) is a hematological cancer characterized by accumulation of malignant plasma cells in the bone marrow. The patients are immune suppressed and suffer from recurrent and chronic infections. Interleukin-32 is a non-conventional, pro-inflammatory cytokine expressed in a subgroup of MM patients with a poor prognosis. IL-32 has also been shown to promote proliferation and survival of the cancer cells. Here we show that activation of toll-like receptors (TLRs) promotes expression of IL-32 in MM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The MM cell line RPMI-8226 expresses a broad range of TLRs ( 23 ) including TLR4 and TLR9, which were also expressed in a high proportion of the primary MM cells. In line with previously published data ( 22 , 25 , 27 29 ), we found that both cell proliferation ( Figure 1C ) and cell viability ( Figures 1D, E ) were increased following LPS and CpG treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The MM cell line RPMI-8226 expresses a broad range of TLRs ( 23 ) including TLR4 and TLR9, which were also expressed in a high proportion of the primary MM cells. In line with previously published data ( 22 , 25 , 27 29 ), we found that both cell proliferation ( Figure 1C ) and cell viability ( Figures 1D, E ) were increased following LPS and CpG treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The MM cell line RPMI-8226 was obtained from the American Type Culture Collection (ATCC; Rockville, MD, USA). RPMI-8226 cells depleted for TLR4 (TLR4 KO), TLR9 (TLR9 KO), and control/mock (WT) cells were generated by gene editing using CRISPR/Cas9 as previously described ( 23 ). The cells were cultured in RPMI-1640 medium with 20% heat-inactivated fetal calf serum (FCS) during expansion and 10% FCS for experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…OH-2 and IH-1 were established in our laboratory ( 16 , 17 ). The cells were cultured in RPMI-1640 medium with fetal calf serum or human serum as previously described ( 18 ). For T-cell isolation and activation, human PBMCs were isolated from buffy coat using Lymphoprep (Stem Cell Technologies, Vancouver, Canada) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%